Ответ:
[tex]f(x) = \frac{3x}{ {x}^{2} - 4 } [/tex]
[tex]f( - x) = \frac{3( - x)}{ {( - x)}^{2} - 4} [/tex]
[tex]f( - x) = \frac{3( - x)}{ {x}^{2} - 4} [/tex]
[tex]f( - x) = - \frac{3x}{ {x}^{2} - 4} [/tex]
[tex]f( - x) = - f(x)[/tex]
Нечётная
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]f(x) = \frac{3x}{ {x}^{2} - 4 } [/tex]
[tex]f( - x) = \frac{3( - x)}{ {( - x)}^{2} - 4} [/tex]
[tex]f( - x) = \frac{3( - x)}{ {x}^{2} - 4} [/tex]
[tex]f( - x) = - \frac{3x}{ {x}^{2} - 4} [/tex]
[tex]f( - x) = - f(x)[/tex]
Нечётная